The Management of Municipalities Is Also Management of the State (Observatorio Económico, 2016)
There is much talk of citizens' distrust of government, politics, and their institutions. Every person's real, everyday experience of the exercise of government begins in their closest and most vital space, which is generally the one administered by municipal government. It is the municipality that intervenes in the administration of health care, in public primary and secondary education, in cleaning services and the upkeep of public spaces, and in social, cultural, recreational, and sports programs, among others. Continue reading...
Keywords: state management; municipal management